Family Ownership and Accrual-Based Earnings Management: Evidence from Tunisia - Atika Ben Gamra; Dorra Ellouze (Asian Academy of Management Journal of Accounting and Finance, 2021)
The aim of this paper is to investigate the effect of family shareholding and chief executive officer (CEO) characteristics on earnings management. We use panel data for a sample of 37 Tunisian non-financial listed firms over the period 2007–2017. We contribute to the literature on corporate governance in family firms by testing the effect of the presence of a family or a founder CEO on earnings management in Tunisia. Our results show that the family ownership and the presence of a family CEO (either founder or not) are positively and significantly associated with earnings management practices. These findings suggest that families’ dominance with a significant equity stake and a CEO position under control leads to an entrenchment effect resulting in poor earnings reporting quality.